Simple Financial Statements For Individual Companies: Concepts and Technicues Based on Mapalus Philosophy - Anneke WANGKAR; Claudia Wanda Melati KOROMPIS; I Dewa Ayu KRISTIANTARI (Indonesia Strategic Sustainability, 2022)
The author aims to provide a concept and technique of simple financial reporting and introduce the benefits of financial accountability. Authors use a qualitative method or approach with phenomenological studies. Mapalus philosophy is appointed to create a concept and technique of financial accountability for the business of an independent, non -manipulative, and objective individual company. The results of this study are expected to contribute to policymakers and especially respective business owners to report their business results as well as possible through techniques and simple and easy-to-understand strategies and ways.